Systematic Literature Review about Mineral Resources and Geotechnics Management: Generate Research Trends - Andy Erwin Wijaya; Ratnasari, Ririn Tri; Ismail, Shafinar (UIR PRESS, 2024)
The majority of developing nations' mining industries are linked to high waste rates, poor use of resources, and serious ecological and environmental issues. Finding effective ways to use recyclable and clean natural resources through scientific and technological innovation is a key goal for these nations. The goal of this study is to offer a thorough overview of the most significant developments in mineral resource research during the past few decades, along with recommendations for more research. Through the use of a Systematic Literature Review (SLR), this study methodology yields the key conclusion that, in order to minimize risk, stakeholders must appropriately manage mineral resources, which is a necessary basis for social and economic growth. Sustainability and the mining industry are linked by current research trends.